Evaluation of Physics Textbooks - Kapanadze, Marika; Jonas-Ahrend, Gabriela; Mazzolini, Alexander; Joubran, Fadeel (The International Handbook of Physics Education Research: Special Topics)
Physics textbooks are generally viewed as important tools that provide well-presented and reliable information that supports and enhances students' understanding of critical concepts. The main goal of this chapter is to find out what attention has been given to textbook evaluation in physics education research literature. Studies about physics textbooks from different countries and different eras are discussed and analyzed, and a broad overview about aspects that influence the efficacy of physics textbooks are presented. Research papers that discuss the importance and influence of digital textbooks (and similar technological resources) are also analyzed.

Echtzeitfähige Modellierung eines innovativen Drückwalzprozesses für die eigenschaftsgeregelte Bauteilfertigung - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (at - Automatisierungstechnik)
Zusammenfassung Aufgrund aktueller Transformationsprozesse kommt der automatisierten und ressourceneffizienten Fertigung hochfester Leichtbauteile eine steigende Bedeutung zu, beispielsweise im Flugzeug- und Fahrzeugbau. Für kleine Losgrößen bietet sich hier insbesondere das Fertigungsverfahren des Drückwalzens an. Der konventionelle, industriell genutzte Drückwalzprozess stößt allerdings aufgrund der Prozesskomplexität hinsichtlich der Reproduzierbarkeit an seine Grenzen. Dies wird in der Praxis teilweise durch personengebundenes Erfahrungswissen kompensiert. Auch ist es nicht möglich, Bauteileigenschaften definiert einzustellen. Aus diesem Grund bietet der Einsatz einer neuartigen Eigenschaftsregelung Chancen zur Weiterentwicklung des Fertigungsprozesses und die Möglichkeit zur Prozessautomatisierung. Hier werden die Werkzeugbahnen abhängig einer Online-Eigenschaftsmessung über eine zusätzliche Reglerkaskade manipuliert. Die Entwicklung einer solchen Eigenschaftsregelung erfordert den Einsatz geeigneter, modellbasierter Entwurfsmethoden. In diesem Beitrag wird daher ein regelungstechnisches Systemmodell für das Drückwalzen metastabiler austenitischer Edelstähle vorgestellt. Das Simulationsmodell weist aufgrund seiner Echtzeitfähigkeit neben dem Einsatz als reines Entwurfsmodell weitere Nutzungsmöglichkeiten z.B. in Beobachtern auf und grenzt sich somit von domänenspezifischen Simulationstools wie der FEM ab.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Control strategy for angular gradations by means of the flow forming process - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Materials Research Proceedings)
Abstract. Climate change, rare resources and industrial transformation processes lead to a rising demand of multi-complex lightweight forming parts, especially in aerospace and automotive sectors. In these industries, flow forming is often used to produce cylindrical forming parts by reducing the wall thickness of tubular semifinished parts, e.g. for the production of hydraulic cylinders or gear shafts. The complexity and functionality of flow forming workpieces could be significantly increased by locally graded microstructure and geometry structures. This enables customized complex hardness distributions at wear surfaces or magnetic QR codes for a unique, tamper-proof product identification. The production of those complex, 2D (axial and angular) graded forming parts currently depicts a great challenge for the process and requires new solutions and strategies. Hence, this paper proposes a novel control strategy that includes online measurements from an absolute encoder to determine the angular workpiece position. Workpieces of AISI 304L stainless steel with 2D-graded structures are successfully manufactured using this new strategy and analyzed regarding the possible accuracy and resolution of the gradation. At this point, a dependency of the gradations on the sensor and actuator dynamics, accuracy and geometry could be noted. It is further evaluated how the control strategy could be extended by an observer-based closed-loop property control approach to enhance the accuracy of the suggested strategy.

Teacher Educators' Experiences and Expressions of Emotion During the Pandemic: International Perspectives - Newberry, Melissa; Rizvi, Meher; van der Want, Anna; Jonas-Ahrend, Gabriela; Kaldi, Stavroula; Kihara, Toshiyuki; Franco, Juan Vicente Ortiz; Ratnam, Tara (Advances in Research on Teaching)

Detection of phase transformation during plastic deformation of metastable austenitic steel AISI 304L by means of X-ray diffraction pattern analysis - Rozo Vasquez, Julian; Arian, Bahman; Kersting, Lukas; Walther, Frank; Homberg, Werner; Trächtler, Ansgar (Metals)

The affective response following autogenic training - Thorenz, Kristin; Berwinkel, Andre; Weigelt, Matthias (Leistung steuern. Gesundheit stärken. Entwicklung fördern.)

Living the Dream? Relating to the living conditions of Hispanic migrants in California through the short story Inside Out - Methfessel, Annette; Janzen, Thomas (Englisch betrifft uns)

Konstruktionen in der prozedurenorientierten Schreibdidaktik. - Rezat, Sara (Die Konstruktion stärken: Ein Handlungsfeld der Deutschdidaktik neu betrachtet)

Contrastiveness in the context of action demonstration: an eye-tracking study on its effects on action perception and action recall - Singh, Amit; Rohlfing, Katharina J. (Proceedings of the Annual Meeting of the Cognitive Science Society 45 (45))
The study investigates two different ways of guiding the addressee of an explanation - an explainee, through action demonstration: contrastive and non-contrastive. Their effect was tested on attention to specific action elements (goal) as well as on event memory. In an eye-tracking experiment, participants were shown different motion videos that were either contrastive or non-contrastive with respect to the segments of movement presentation. Given that everyday action demonstration is often multimodal, the stimuli were created with re- spect to their visual and verbal presentation. For visual presentation, a video combined two movements in a contrastive (e.g., Up-motion following a Down-motion) or non-contrastive way (e.g., two Up-motions following each other). For verbal presentation, each video was combined with a sequence of instruction descriptions in the form of negative (i.e., contrastive) or assertive (i.e., non-contrastive) guidance. It was found that a) attention to the event goal increased for this condition in the later time window, and b) participants’ recall of the event was facilitated when a visually contrastive motion was combined with a verbal contrast.
Keywords: Attention; negation; contrastive guidance; eye-movements; action understanding; event representation

An Integrative View of the Transformations towards Sustainability and Digitalization: The Case for a Dual Transformation - Kürpick, Christian; Rasor, Anja; Scholtysik, Michel; Kühn, Arno; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Burst Mode of Ultrasonic Resonant Oscillations for Stimulation and Destruction of Tumor Cells - Sehlmeyer, Birte; Kampmann, Rebecca; Scheidemann, Claus; Hemsel, Tobias; Getzlaff, Mathias (Frühjahrstagung 2023, Sektion Kondensierte Materie (SKM))

Burst Mode Characteristics of an Ultrasonic Transducer for Treatment of Cancer Cells - Kampmann, Rebecca; Sehlmeyer, Birte; Scheidemann, Claus; Hemsel, Tobias; Getzlaff, Mathias (Frühjahrstagung 2023, Sektion Kondensierte Marterie (SKM))

Single-shot spatial instability and electric control of polariton condensates at room temperature - Gao, Ying; Ma, Xuekai; Zhai, Xiaokun; Xing, Chunzi; Gao, Meini; Dai, Haitao; Wu, Hao; Liu, Tong; Ren, Yuan; Wang, Xiao; Pan, Anlian; Hu, Wei; et al. (arXiv:2305.01368)
In planar microcavities, the transverse-electric and transverse-magnetic (TE-TM) mode splitting of cavity photons arises due to their different penetration into the Bragg mirrors and can result in optical spin-orbit coupling (SOC). In this work, we find that in a liquid crystal (LC) microcavity filled with perovskite microplates, the pronounced TE-TM splitting gives rise to a strong SOC that leads to the spatial instability of microcavity polariton condensates under single-shot excitation. Spatially varying hole burning and mode competition occurs between polarization components leading to different condensate profiles from shot to shot. The single-shot polariton condensates become stable when the SOC vanishes as the TE and TM modes are spectrally well separated from each other, which can be achieved by application of an electric field to our LC microcavity with electrically tunable anisotropy. Our findings are well reproduced and traced back to their physical origin by our detailed numerical simulations. With the electrical manipulation our work reveals how the shot-to-shot spatial instability of spatial polariton profiles can be engineered in anisotropic microcavities at room temperature, which will benefit the development of stable polariton-based optoeletronic and light-emitting devices.

Photochemical reaction enabling the engineering of photonic spin-orbit coupling in organic-crystal optical microcavities - Liang, Qian; Ma, Xuekai; Ren, Jiahuan; Long, Teng; Gu, Chunling; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (arXiv:2309.07652)
The control and active manipulation of spin-orbit coupling (SOC) in photonic systems is fundamental in the development of modern spin optics and topological photonic devices. Here, we demonstrate the control of an artificial Rashba-Dresselhaus (RD) SOC mediated by photochemical reactions in a microcavity filled with an organic single-crystal of photochromic phase-change character. Splitting of the circular polarization components of the optical modes induced by photonic RD SOC is observed experimentally in momentum space. By applying an ultraviolet light beam, we control the spatial molecular orientation through a photochemical reaction and with that we control the energies of the photonic modes. This way we realize a reversible conversion of spin-splitting of the optical modes with different energies, leading to an optically controlled switching between circularly and linearly polarized emission from our device. Our strategy of in situ and reversible engineering of SOC induced by a light field provides a promising approach to actively design and manipulate synthetic gauge fields towards future on-chip integration in photonics and topological photonic devices.

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (arXiv:2303.12593)
Topological states have been widely investigated in different types of systems and lattices. In the present work, we report on topological edge states in double-wave (DW) chains, which can be described by a generalized Aubry-Andr\'e-Harper (AAH) model. For the specific system of a driven-dissipative exciton polariton system we show that in such potential chains, different types of edge states can form. For resonant optical excitation, we further find that the optical nonlinearity leads to a multistability of different edge states. This includes topologically protected edge states evolved directly from individual linear eigenstates as well as additional edge states that originate from nonlinearity-induced localization of bulk states. Extending the system into two dimensions (2D) by stacking horizontal DW chains in the vertical direction, we also create 2D multi-wave lattices. In such 2D lattices multiple Su-Schrieffer-Heeger (SSH) chains appear along the vertical direction. The combination of DW chains in the horizontal and SSH chains in the vertical direction then results in the formation of higher-order topological insulator corner states.

Tweaking Spectral Topology and Exceptional Points by Nonlinearity in Non-Hermitian Polariton Systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (arXiv:2305.04855)
Exceptional points (EPs) with their intriguing spectral topology have attracted considerable attention in a broad range of physical systems, with potential sensing applications driving much of the present research in this field. Here we theoretically demonstrate the realization of EPs in a system with significant nonlinearity, a non-equilibrium exciton-polariton condensate. With the possibility to control loss and gain and nonlinearity by optical means, this system allows for a comprehensive analysis of the interplay of nonlinearities (Kerr-type and saturable gain) and non-Hermiticity. Not only do we find that EPs can be intentionally shifted in parameter space by the saturable gain, we also observe intriguing rotations and intersections of Riemann surfaces, and find nonlinearity-enhanced sensing capabilities. Our results are quite general in nature and illustrate the potential of tailoring spectral topology and related phenomena in non-Hermitian systems by nonlinearity.

Entwicklung und Evaluation einer NdN-Unterrichtsreihe zur Unterstützung von Lernpfaden - Webersen, Yvonne (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Qualifizierungsbedarf des Bildungspersonals mit besonderem Fokus auf Selbstinszenierungspraktiken von Jugendlichen im Übergang Schule-Beruf - Otto, Franziska; Kundisch, Heike (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Rezension zu: Landgraf-Freudenreich, Verena: Ästhetik des Brauchtums. Eine empirische Betrachtung deutscher Schützenfestschriften, Bielefeld 2022. - Leineweber, Jonas (Bayrisches Jahrbuch für Volkskunde)

Motivationsprofile zum Erwerb pädagogischen Wissens im Lehramtsstudium - Homt, Martina; Wehde, Janis; Bloh, Bea